2014
DOI: 10.1111/aeq.12075
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Justice, Reintegration, and Race: Reclaiming Collective Identity in the Postracial Era

Abstract: Restorative justice has gained ascendancy within both judicial systems and educational settings through which court-involved youth are resocialized as part of reintegration intervention. This article explores the conflict over collective representation at the intersections among public education, criminal justice, and restorative intervention. The author argues that restorative intervention must attempt to broaden its cultural reach and implicate the countercultural realities that exist at the margins of socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In her studies of heterogeneous small-group work, Cohen (1994) demonstrated how status inequality often prevails, and is often even reinforced, during interactive group workif the interaction encourages confident students to come to think of themselves, and to be considered by peers, as more valuable contributors to the learning process than quieter or marginalised students. When an alternative pedagogical process such as the restorative justice circle is created for inclusion, status and inequality remain present, and may even become more visible in the context of the ostensible equality of circle members (Utheim, 2014;Wing, 2009). In some cases, as observed in various circle interactions in this study, outgroup members become visible in ways that further entrench their exclusion.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In her studies of heterogeneous small-group work, Cohen (1994) demonstrated how status inequality often prevails, and is often even reinforced, during interactive group workif the interaction encourages confident students to come to think of themselves, and to be considered by peers, as more valuable contributors to the learning process than quieter or marginalised students. When an alternative pedagogical process such as the restorative justice circle is created for inclusion, status and inequality remain present, and may even become more visible in the context of the ostensible equality of circle members (Utheim, 2014;Wing, 2009). In some cases, as observed in various circle interactions in this study, outgroup members become visible in ways that further entrench their exclusion.…”
Section: Discussionmentioning
confidence: 72%
“…Within the specificities of practice, circle norms may evade or silence the feelings, identities and stories of some, while welcoming others: these choices (intentional or not) circulate and normalize unequal power relations. Without critical reflection on how power relations are produced spatially and culturally, restorative pedagogy could unintentionally perpetuate the harm it seeks to remedy (Lustick, 2017;Parker, 2020;Utheim, 2014). This is crucial for democratic development and participation.…”
mentioning
confidence: 99%
“…Other influential scholars in restorative justice are Marshall, Sharpe, and Sullivan and Tifft. Marshall (in Utheim, 2014: 359) defines restorative justice as “a process whereby all the parties with a stake in a particular offense come together to resolve collectively how to deal with the aftermath of the offense and its implications for the future.” This is the definition adopted by the United Nations. Van Ness et al (2001: 5–6) offer an adaptation of Sharpe’s 1998 description, in which restorative justice:…”
Section: Why Restorative Justice?mentioning
confidence: 99%
“…This position is disturbed by interviews included in this article and the insightful contributions of Utheim (2014). Utheim examines how narratives of colorblindness within institutions (schools, but this can be extrapolated to libraries) can reinstate oppressions and harms that restorative justice purportedly addresses.…”
Section: Why Restorative Justice?mentioning
confidence: 99%
See 1 more Smart Citation